Optimalisasi Pencahayaan Alami pada Ruang - Nurhaiza, Nurhaiza; Lisa, Nova Purnama (Arsitekno, 2016)
Abstract Natural lighting is the lighting obtained from direct sunlight, where the light is obtained in the morninguntil late afternoon. According to SNI 03-2396-200, natural lighting during the day can be good in a span of solarorientation starting at 8:00 pm until 16: 00 pm with equitable distribution of incoming light in the room and didnot leave annoying glare effects in the use of lighting natural, regardless of the quality and distribution of lightthat enters the building through a window and orientation of openings. The wider the aperture, the more light thatenters the room. It is necessary to control the amount of light coming into the room. The research used isquantitative method by using mathematical models, with the measurement process, using a formula to obtainaccurate data. The object of research and observations in Architecture Program Faculty Building University ofMalikussaleh, Lhokseumawe Aceh. Observation is by direct observation to see the condition of natural lighting inclassrooms, measurements the extent of the classroom. Then collect some measurement data among other things,measure the light intensity at the lecture hall by using Luxmeter, calculate the intensity of light at the lecture hallby factors sky with measuring point main and the measuring point side and the comparative results of themeasurement of light intensity of the lighting level the average recommended. The results show, a lecture hall inthe building Prodi architecture has three floors, which have 4 lecture room on floors 1 and 2, 2 room studioregular on floors 1, 2 lab computer room on the floor and 2 studio design room on the 2nd floor. also of coursethe building also has other equipment such as administration room, warehouse and other supporting facilities.But for the third floor untapped dikarenaka still in the process of renovation. The results of observations obtainedintensity of natural light on the 1st floor and 2nd floor Architecture Program building University of Malikussalehbased on the measurement of light intensity using the luxmeter, the obtained data is that the rooms was not inaccordance with the standards of an average lighting is recommended by ISO 2000 for classrooms -03 250 luxand 700 lux.Key word: Natural Lighting, Light Intensity, Lux meters, ISO 2000, SNI 03-2396-200